Role of Transaction Cost Economics in Formulating Policy Variables for Growth of Small Poultry Businesses in Tanzania - Alfred Msami, Peter; Ngaruko, Deus (IJRDO - Journal of Business Management, 2016)
The Transaction Cost economics (TCE) provides a suitable conceptual model for identifying factors curtailing growth of small business firms in developing economies.This research paper employs the model and uses poultry farm businesses (PFBs) in the United Republic of Tanzania as representative of thebusinesses.The study aims, at identifying policy variables that can successfully stimulate the businesses to evolve where they do not exist and the existing ones to grow, a problematic topic widely discussed in academics and policy making.A cross-sectional survey was conducted in two regions in the country covering 170 respondents in all Institutional arrangements. Descriptive statistics indicate that market institutional arrangement is relatively inefficient characterized by high transaction costs that curtailgrowth than it is with contractual arrangement; and yet 75 percent, that is majority of the businessfirms opts for market institutional arrangement. A theory based intervention must therefore, be focused oninstituting measures that minimizes transaction cost and maximizes profit.